Delivering love to children: the role of father through food preparation / Mohd Syaquif Yasin Kamaruddin … [et al.] - Yasin Kamaruddin, Mohd Syaquif; Abdul Aziz, Azdel; Ahmad, Noor Azmi; Saiful Bakhtiar, Mohd Faeez; Abd Hanan, Firdaus (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA (UiTM), Malaysia, 2013)
The division of task for both parents has been established long time ago whereby mother is nurturer of love for children while father has always being the breadwinner. But this division slowly altered when factors such as social lifestyle, education and technology change gradually with time. The increasing number of working mother cause by those factors has somehow change the role of father. Liter- ature stated children who have good relationships with their fathers will have an increase in mental development and they turn out to be more sociable. When mother deliver and communicate their love through foodways, it is believed that fathers are able deliver the love equivalent using the same platform.